(untitled) (Journal of Contemporary Studies, 2015)
Abstract Pakistan, since its inception, has been confronting the challenge of national integration due to multi-ethnic and multi-linguisticpopulation residing in the country. These dynamics of the society increase the magnitude of integration related challenges faced by the country. Several intervening internal and external factors tend to create split in social fabric of society thus negatively affecting the process of national integration in Pakistan. Like the other segments of society, the youth of the country is confronted with socio-political and socio-economic issues that tend to affect their feeling of belongingness and cohesiveness. The current situation in Pakistan demands for due involvement of important stakeholders to extend measures for strengthening national integrity among youth. In this regard, the educational institutions can play a significant role in enhancing the cohesion in society in general and youth in particular. Empowerment and morale boosting of youth is pivotal in bringing national harmony in the society. Moreover, it will also equip the youth to cope with the societal problems such as rapidly growing intolerance and schism in the society based on ethnic, cultural, and linguistic differences among masses. This paper aims to highlight the youth as a pivotal agent of national cohesion, the factors that generally affecting national cohesion among Pakistani youth and the role of university education in strengthening national cohesion. Along with highlighting the existing policies to strengthen the national integration at university level,